Numerical Investigation of Flow Patterns and Concentration Profiles in Y‐Mixers. Issue 10 (8th September 2016) - Babu, Harsha Vardhan; Sahu, Swati; Haderlein, Michael; Peukert, Wolfgang; Verma, Nishith
Abstract: The fluid flow patterns and associated concentration fields in Y‐mixers are investigated using lattice Boltzmann method‐based models. The focus lies on the impact of the mixing angle on the flow and concentration fields, with the mixing angle varying between acute ( θ = 10°) and obtuse ( θ = 130°) angles. Residence time distributions are determined to study the effect of the angles on the mixing and velocity patterns, in particular, different flow regimes, i.e., stratified laminar, vortex, and engulfment flow. The results from the simulations are validated with literature data and found to be in good agreement. Maximum mixing occurs in the 100° obtuse‐angle Y‐mixer, attributed to the extensive engulfment of flows in the mixing channel. Abstract : 3D lattice Boltzmann method‐based model simulations were performed to study the flow patterns and concentration distributions in a Y‐mixer for different mixing angles. These simulations identified stratified laminar, vortex, and engulfment flow regimes. The residence time distributions for these flow patterns were characteristically different. Maximum mixing occurred in the 100° obtuse‐angle Y‐mixer.